The impact of different natural environments on the regeneration dynamics of two Nothofagus species across elevation in the southern Andes - Cagnacci, Julieta María; Estravis Barcala, Maximiliano; Lia, Veronica Viviana; Martinez Meier, Alejandro Gabriel; Gonzalez Polo, Marina; Arana, Maria Veronica (Forest Ecology and Management)
A widely accepted paradigm in forest ecology proposes that patterns of relative abundance among mature forest trees are largely influenced by biotic and abiotic processes that operate most intensely during the earliest life-cycle stages. Therefore, traits expressed early in development such as germination and seedling establishment may be under strong selective pressure from the environment, and their adjustment to changing climates may ultimately influence species? responses to global climate change. Here we used different environments established across altitude in an old-growth temperate Patagonian forest as a natural laboratory, and studied the Nothofagus obliqua and N. pumilio regeneration response ? seedling emergence and survival ?to different climatic scenarios, inside and outside their natural distribution range. These are two iconic species of sub-Antarctic forests, which co-exist in contrasting and non-overlapping thermal niches. Whereas N. obliqua is predominant in the warmer and lower environments at 650?850 m above sea level (a.s.l.), N. pumilio inhabits the colder and higher montane environments, above 1000 m a.s.l. By sowing germinated seeds of both species at different altitudes in the forest ? 680, 930 and 1340 m a.s.l. ? we were able to distinguish the environmental influence on seedling emergence from its influence on germination. Our results show that the local environment had a major effect on seedling survival, and a minor influence on emergence. Overall, regeneration of both species showed a temporal window of stronger environmental susceptibility, which comprised the process of emergence, and in the particular case of N. obliqua, the first month of post-emergence growth. Survival ability was influenced by the ontogenetic stage of the seedling, evidencing stronger environmental resistance and higher probability of survival after the first year of growth. Interestingly, we found inter-specific differences in survival dynamics and the final number of surviving seedlings, which may reflect ...